ISLAM MESIR: ASAL-USUL, PERKEMBANGAN DAN CORAK PEMIKIRAN KEISLAMAN - Faza, Asrar Mabrur (Jurnal Ilmu Ushuluddin, 2012)
This paper raised about Islamic thought patterns that exist in Egypt.According to the authors, the teachings of supplement Islam derived fromhistorical scenarios in a vulnerable time and place as in Egypt, was part ofthe perspective view of Islam as a historical religion. Therefore, the arrivalof Islam, the development and emergence of the Muslims in the fieldof modern thought in this country has its own uniqueness. The leaders ofthe Muslims during the military expansion of Egypt, from the beginninghas been offering the limits of interfaith tolerance. Some of the powerfulempires that ever existed in Egypt has contributed significantly to the constructionof Islamic civilization at that time. Egyptian Islamic thinkersboth modern and contemporary style has provided the liberal Islamicthought in that country. So that, it could be an example for other countriesin the development of Islamic thought in general.